A fast, comprehensive screening method for doping agents in urine by gas chromatography–triple quadrupole mass spectrometry - Van Eenoo, Peter; Van Gansbeke, Wim; De Brabanter, Nik; Deventer, Koen; Delbeke, Frans T. (Journal of Chromatography A, 2011)
The use of performance enhancing drugs in sports is prohibited. For the detection of misuse of such substances gas chromatography or liquid chromatography coupled to mass spectrometry are the most frequently used detection techniques. In this work the development and validation of a fast gas chromatography tandem mass spectrometric method for the detection of a wide range of doping agents is described. The method can determine 13 endogenous steroids (the steroid profile), 19-norandrosterone, salbutamol and 11-nor-Δ9-tetrahydrocannabinol.9carboxylic acid in the applicable ranges and to detect qualitatively over 140 substances in accordance with the minimum required performance levels of the World Anti-Doping Agency in 1 ml of urine. The classes of substances included in the method are anabolic steroids, β2-agonists, stimulants, narcotics, hormone antagonists and modulators and beta-blockers. Moreover, using a short capillary column and hydrogen as a carrier gas the run time of the method is less than 8 min.